Is there a correlation among landing stability, ankle dorsiflexion range of motion, and ankle stiffness during single-leg landing? - Mohamadreza Hatefi; Mahdis Biglari; Farideh Babakhani (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background Even though both landing stability and ankle dorsiflexion stiffness (ankle DR-stiffness) have been independently identified as risk factors associated with non-contact injuries, no study has specifically investigated the relationship between these two variables. Methods Twenty male recreational athletes volunteered to participate in this study. Their ankle DF-ROM based on the weight-bearing lunge test, and landing stability based on the dynamic postural stability index (DPSI) and time to stabilization (TTS) were evaluated during a single-leg landing (SLL). Results There was no statistically significant difference among ankle DF-ROM, ankle DF-stiffness, DPSI, and TTS during the SLL task (p > .05). Although a moderately positive relationship was observed between ankle DF-ROM and ankle DF-stiffness (p = .177; r = .354 [95% CI, -.153 to .653]) and a moderately negative relationship between ankle DF-ROM and TTS (p = .163; r = -.375 [95% CI, -.598 to .098]), these were not statistically significant. Conclusion The findings indicate that ankle DF-stiffness as an independent variable, does not significantly affect landing stability based on the TTS and DPSI indexes. However, its interaction with other variables, such as sex, age, and the nature of the movement task, may influence landing stability. This study area warrants further research.